The Standardization System of Water Conservancy Project Cost Management under the EPC General Contract Mode. Issue 1 (June 2021) - Li, Sha; Wang, Yijia; Zeng, Yu
Abstract: It is the development trend for water conservancy project to adopt EPC general contract mode. The realization of scientific and effective project cost management under total price contract is the key to guarantee the contractor's economic benefit. Based on the contractor's perspective, this paper sorts out the content of cost management at each stage, clarifies the responsible subject of cost management at each stage, and explores the construction of cost management standardization system.